The Role Of Fear Of Missing Out In Mediating The Influence Of Hedonic Motivation On Compulsive Buying (Study On Marketplace Users In Denpasar City) - Komang Gd Cahya Wiguna; Ni Made Asti Aksari; Gede Bayu Rahanatha; I Nyoman Nurcaya (Journal Of Social Science (JoSS), 2025)
Digital transformation has changed consumer behavior patterns, including an increase in marketplace users that encourage compulsive buying behavior among generation Z. Data from the Ministry of Trade of the Republic of Indonesia in 2024 shows that the number of marketplace users will increase from 38.72 million in 2020 to 58.63 million in 2023 and is predicted to reach 99.1 million in 2029. This study aims to determine the influence of hedonic motivation on compulsive buying and test the role of fear of missing out (FoMO) as a mediating variable. The research was conducted in Denpasar City with a quantitative approach and purposive sampling method on 100 marketplace user respondents. The analysis technique used is path analysis. The results of the study showed that hedonic motivation had a positive and significant effect on compulsive buying and FoMO. FoMO also has a positive and significant effect on compulsive buying and partially mediates the relationship between hedonic motivation and compulsive buying. The conclusions of this study show that hedonic motivation and FoMO play an important role in encouraging excessive shopping behavior in the marketplace.